Direito compreensivo: além dos horizontes da disputa - Thais Lopes Chacara de Aguilar (2014)
Thedissertation has the purpose ofrevealingthe truth about the Comprehensive Law Movement, inanintegrative, restorative, humanistic, therapeutic e transdisciplinaryway.From the belief in the possibility toovercome thejurisdictional provisionsdifficulties, it was investigated the attorney,as in the academic field, as in thenon-juridical society, to make suggestions about changes in Legal Educationin Brazil,from the perspective ofthemtranslate modifications in the lawyers attitude towards the conflict,asa pathto give to this professional wide opportunitiestoact by the Legal System, keepingthe confidence, the respect and the ethic in his or herprofessional or personal trajectory.The hypothesis will be tested through amainly theoretical investigation, prioritizingthe elaborationof peculiar conceptual schemes anddiscursive-argumentative processes that will contribute to the convincement about the validity of the proposals showedonthis dissertation.